The worlds of the preacher : navigating biblical, cultural, and personal contexts - Gibson, Scott M., 1957- (Grand Rapids, MI : Baker Academic, a division of Baker Publishing Group, 2018)
Building on Haddon Robinson's philosophical approach to preaching, this book brings together accomplished evangelical preachers and teachers to help students and pastors understand the worlds--biblical, cultural, and personal--that influence and impact their preaching. The contributors explore the various inner and outer worlds in which a preacher functions with the goal of helping preachers sharpen their craft. -- ‡c From publisher's description.
Introduction: A tribute to Haddon Robinson / Scott M. Gibson -- The worlds of the preacher / Haddon W. Robinson -- The preacher and the world of the Old Testament / Steven D. Mathewson -- The preacher and the world of the New Testament / Duane Litfin -- The preacher's personal world / Scott M. Gibson -- The world of ethnic and cultural issues in preaching / Matthew D. Kim -- The worlds of the listener / Jeffrey Arthurs -- Preaching in this present world / Patricia M. Batten -- The mission of preaching in this world / Victor D. Anderson -- The world of history and the task of preaching / Scott Wenig -- Preaching to a culture dominated images / Donald R. Sunukjian -- Afterword: The worlds of the preacher / Scott M. Gibson.
Includes bibliographical references.
Keywords: Preaching